1980
DOI: 10.1115/1.3263304
|View full text |Cite
|
Sign up to set email alerts
|

Design of Radial Nozzles in Cylindrical Shells for Internal Pressure

Abstract: A design method is presented that allows a designer to predict the maximum allowable working pressure of an opening reinforcement using an allowable stress basis. Primary application of the method is directed toward large openings as defined by ASME Section VIII, Division 1, paragraph UA-7. Recent hydrotests conducted on several production pressure vessels have demonstrated that existing paragraph UA-7 area replacement rules are inadequate in certain d/D and D/T ranges. The inadequate designs were initially in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Study in repad design has been recorded since 1970s by [7][8] and [12][13] performed parametric and numerical study while [10][11] performed experimental studies on various repad design. Beginning of 1990s, FEA has been used as tool to perform the analysis for repad at nozzle of pressure vessels [14].…”
Section: Repad Design and Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Study in repad design has been recorded since 1970s by [7][8] and [12][13] performed parametric and numerical study while [10][11] performed experimental studies on various repad design. Beginning of 1990s, FEA has been used as tool to perform the analysis for repad at nozzle of pressure vessels [14].…”
Section: Repad Design and Developmentmentioning
confidence: 99%
“…Earlier works by [10] had performed experiment on prototype pressure vessel with repad thickness of 14.3 mm carbon steel material installed outside the vessel. It was found that the used of repad had reduced the stress from internal pressure.…”
Section: F Fem and Experiments On Repad By Othersmentioning
confidence: 99%